Portraits of the New Man: revolutionary subjectivity in Episodes of the Cuban Revolutionary War and “The parade begins” (Anclajes, 2013)
The New Man ideal depicted on Ernesto “Che” Guevara’s Episodes of the Cuban Revolutionary War, and invoked as a social model in the discourse of the new revolutionary Cuban state after 1959 is taken here as a reference for reading Reinaldo Arena’s short story “The parade begins”. Contrary to Guevara’s text, Arenas proposes that the revolutionary event does not mean the final de-alienation and emancipation of the repressed original subject, but the chance of opening up a space that allows to escape from the socially prescribed identities (man, warrior, hero) and explore new possible forms of subjectivity.
Keywords: Reinaldo Arenas; Ernesto “Che” Guevara; Cuban literature; Literary criticism; Cuban revolution